Femtosecond dynamics of photoexcited C60 films - Causa', M; Ramirez, I; Hardigree, J; Riede, M; Banerjii, N (American Chemical Society, 2018)
The well-known organic semiconductor C60 is attracting renewed attention due to its centimetre-long electron diffusion length and high performance of solar cells containing 95% fullerene. Yet, its photophysical properties remain poorly understood. Here, we elucidate the dynamics of Frenkel and intermolecular (inter- C60) charge transfer (CT) excitons in neat and diluted C60 films from high quality femtosecond transient absorption (TA) measurements, performed at low fluences and free from oxygen or pump-induced photo-dimerization. We find from preferential excitation of either species that the CT excitons give rise to a strong electro-absorption signal but are extremely short-lived. The Frenkel exciton relaxation and triplet yield depend strongly on the C60 aggregation. Finally, TA measurements on full devices with applied electric field allow us to optically monitor the dissociation of CT excitons into free charges for the first time and to demonstrate the influence of cluster size on the spectral signature of the C60 anion.